Romani People as Object and Subject of Scientific Inquiry : Scientification of Roma or RomaNization of science? (Liverpool University Press, 2024)
The special issue of Romani Studies entitled “Romani people as object and subject of scientific inquiry: Scientification of Roma or RomaNization of science?” brings forward innovative approaches to critically revise the most disseminated epistemic platforms for studying the past and the presence of Romani people. This collection should be accepted as a step to overcoming the contemporary epistemic crisis in studying minorities which stems from opposition of two extremes, namely, relegating the specifics of social groups on the margins of research interest in order to avoid the risk of essentialization and privileging the voices of those on “periphery” as the exclusively endowed with the right to produce knowledge. Instead struggling with this clearly false dilemma, we offer the range of highly contextualized cases of epistemic neglect or injustice that Romani people expose and the strategies to reestablish justice in producing knowledge regarding this group. Die Sonderausgabe von Romani Studies mit dem Titel „Roma als Objekt und Subjekt wissenschaftlicher Forschung: Verwissenschaftlichung der Roma oder RomaNisierung der Wissenschaft?“ stellt innovative Ansätze vor, um die am weitesten verbreiteten epistemischen Plattformen zur Erforschung der Vergangenheit und Gegenwart der Roma kritisch zu überarbeiten. Diese Sammlung sollte als ein Schritt zur Überwindung der gegenwärtigen epistemischen Krise bei der Erforschung von Minderheiten angesehen werden, die aus dem Gegensatz zweier Extreme resultiert, nämlich der Verbannung der Besonderheiten sozialer Gruppen an den Rand des Forschungsinteresses, um das Risiko einer Essentialisierung und Privilegierung der Minderheiten zu vermeiden Stimmen derjenigen an der „Peripherie“, die ausschließlich das Recht haben, Wissen zu produzieren. Anstatt mit diesem offensichtlich falschen Dilemma zu kämpfen, bieten wir eine Reihe stark kontextualisierter Fälle epistemischer Vernachlässigung oder Ungerechtigkeit an, die Roma aufdecken, und die Strategien zur Wiederherstellung der Gerechtigkeit bei der Wissensproduktion über diese Gruppe.